The Study of Prototypes for Developing Content Marketing Strategies Adding Value: Business in Banana Products - Cobal, Rungthip; Duangsai, Supasee; Polsri, Jintana; Kaewkerd, Phatthira; Kannikaklang, Nikorn; Kanraweekultana, Natratanon (Suan Dusit Graduate School Academic Journal, 2023)
The purpose of this research was to study the prototype and suggest guidelines for developing content marketing strategies adding value: business in banana products. The mixed method research was employed, including quantitative and qualitative researches. The sample of experts, academics and the private sectors who had experience in digital marketing strategies were recruited by purposive sampling. The qualification of 21 commentators included a master's degree or higher, research experience and at least 7 years of expertise in the context. Then, data was collected by the feasibility and potential phototype evaluation forms in 5-level Likert Scale. Then, the validity of the questionnaire was examined by using Item-Objective Congruence Index: IOC and the data was analyzed by descriptive statistics including mean and standard deviation to compare the suitability and feasibility of the developed prototype from the research. The results revealed that the suitable and potential factors for the prototype development was the quality dimension factor, followed by the value dimension factor and content dimension facto, respectively. Therefore, the prototype and suggest guidelines for the study of developing content marketing strategies adding value: business in banana products, which were appropriate and feasible in terms of operational plans, communication methods, content, tools, and transfer of knowledge to the community can lead to a competitive advantage in the future